Preparação e caracterização de nanopartículas contendo o extrato otimizado do coproduto semente do maracujá e avaliação das atividades fotoprotetora e citotóxica/antitumoral - Santos, Grazielle Jesus dos (2022)
The coproduct of passion fruit seed, from the production of juices, is a source of bioactive compounds, such as phenolic compounds, and the study of their extraction is of extreme importance, because they are substances that present several biological activities, including antioxidant and antitumor. The encapsulation of extracts has been used in order to increase the stability and bioavailability of bioactive compounds. The objective of this work was to optimize the extraction process of bioactive compounds from the coproduct passion fruit seeds, using the methods of dynamic maceration, ultrasonic and microwave extraction. Different proportions of hydroethanolic solvent, time and temperature were evaluated. The extracts were evaluated for antioxidant activity by DPPH free radical scavenging and Fe II chelating ability methods. For solvent optimization, performed by dynamic maceration, the extract prepared with ethanol:water 80:20 (v/v) showed the best antioxidant responses. An experimental planning, varying time and temperature, was performed for the optimization by dynamic maceration. The conditions that provided the extract with the highest antioxidant potential were: 41 minutes and 45.0 ºC. The experimental design did not fit the models for the DPPH and chelating ability tests. The best condition for ultrasound extraction was 45.0 ºC and 15 minutes and for microwave extraction, 2 minutes. The best extracts were evaluated for their antioxidant activity by the ABTS method, phenolic compounds were determined by the Folin-Ciocalteau method, and flavonoid content was quantified using AlCl3, with the best responses for ultrasonic, microwave, and ultrasonic extraction, respectively. The extracts were characterized by mass spectrometry. The fatty acids, linoleic, oleic and palmitic, were identified by the full scan method and phenolic acids and flavonoids, the major compound being piceatannol, by the multiple reaction monitoring method. The extract obtained by ultrasonication was chosen for the production of zein-sodium-caseinate and zein-sodium-caseinate-chitosan nanoparticulate systems. The nanoparticles were characterized for size, zeta potential and polydispersity index using Dynamic Light Scattering technique. The extract nanoparticles obtained at zein-sodium chitosan-chitosan mass ratios (1:0.8:0.025) showed better encapsulation efficiency (90.59%). These were coated with chitosan, showing better parameters at the concentration of 0.10% (1:0.8:0.17:0.025). The extracts optimized by the three methods were analyzed for their photoprotective activity by determining the sun protection factor. All showed values above the minimum required by ANVISA, being 18.22; 11.68 and 18.84, respectively, for the extracts obtained by maceration, ultrasound and microwave, suggesting their incorporation in dermocosmetic formulations. The free and encapsulated extracts were evaluated for cytotoxic/antitumor potential against human uterine colo tumor cells (SIHA). The extract-loaded zein-sodium caseinate-chitosan nanoparticulate systems showed cytotoxic/antiproliferative effect at the 48-hour time point for the concentrations of 10, 100 and 200 μg mL-1. The results demonstrated that the passion fruit seed coproduct extracts and the zein-sodium caseinate-chitosan nanoparticulate system loading the extract have potential for application in the pharmaceutical and cosmetic industry.